The shape of the building and its aesthetic elements in the Abbasid era and its reflections on international architecture (the minaret of the Caliph Al-Mu’tasim Billah Mosque in the city of Samarra): شَكل البناء وعناصره الجمالية في العصر العباسي وانعكاساته على الفن المعماري العالمي (مَئذنة جامع الخليفة المُعتصم بالله في مدينة سامراء) - Saad jihad ATTIYA (Journal of engineering sciences and information technology, 2021)
Aquest estudi té com a objectiu aportar llum sobre els elements estètics inherents a la forma constructiva In the Abbasid era, the Islamic caliphate and its historical roots go back to the Mesopotamian civilization located on the same land and ocean. The effect of its architectural forms on the modern architectural installations found in these unique architectural forms has a historical dimension. A topic for starting in order to create new influenced forms Characteristics, shapes and elements of Islamic architecture. It also aims to know the extent of interest and keenness to visit and study the effects of Islamic civilization in the city of Samarra by researchers and architects in the world, and to publish studies and research on it as an element of art and civilization in the world. And the aesthetic and constructional meanings it carries, and the scientific dimensions related to land, climate, construction materials, the environment, and the way people live and settle in a civilized environment that has sources of stable living. The sources were selected on the basis of books, studies related to the city of Samarra and its religious character, which is famous for the antiquities of Islamic civilization, in addition to some websites and field visits. With the study of all the elements available on this part of the land, which prompted the Caliph Al-Mu’tasim Billah to choose it, many factors, including the military, because he wanted this city to be a camp for his soldiers, where the climate is moderate and its lands located on the Tigris River. Together, these elements may have driven the building in the siting and construction of cities by architects and experts. The most important goal of the Caliph in building this city was to build the largest mosque and the highest minaret at that time, the minaret with its style taken from the shape of temples (ziggurats) or the Tower of Babel that appeared in the Mesopotamian civilization, where the minaret took the spiral shape that rotates counter-clockwise. This research deals with the aesthetic meanings in the form of the building and the study of shadow and light, which is one of the reasons for the distinction and uniqueness of the form, and in the end its inheritance. Because the beauty of the form is combined with its use and thus leads to an aesthetic utilitarian function. Art is the mirror of society. This effect reflects the well-being and progress of society in that historical era. Whereas, history has a historical orientalism and the aesthetic has orientalism This city included all the elements and building codes in choosing the site that came from a continuous study and inspection by the Abbasid Caliph Al-Mu’tasim Billah who built an integrated city that contained markets, schools, housing houses, military barracks, walls and places of worship. The most important of them was the Great Mosque and its long minaret, which was distinguished by an architectural and aesthetic innovation and recorded the birth of a decorative art, the tawariq (arabesco), which is inherited to this day.